Stochastic population processes analysis, approximations, simulations - Renshaw, Eric. (Oxford : Oxford University Press, 2011)
This reference text presents stochastic processes and a range of approximation and simulation techniques for extracting behavioural information in the context of stochastic population dynamics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Population -- Statistical methods; Markov processes